Tingkat Motivasi Belajar IPA Pada Siswa Kelas III, IV dan V SD Qita Purwokerto - Devi Ambarwati; Lucky Nindi Riandika Marfu'i (Jurnal Pembelajaran dan Pendidikan Dasar, 2025)
This study aims to examine the level of learning motivation in Natural Science (IPA) among third, fourth, and fifth-grade students at SD Qita Purwokerto. A descriptive quantitative approach was employed, using a learning motivation questionnaire consisting of several closed-ended statements. The respondents comprised 28 students: 11 from grade III, 9 from grade IV, and 8 from grade V. The data were analyzed using percentage techniques to classify motivation levels into four categories: very high, high, moderate, and low. The results revealed that overall, students' learning motivation fell into the high to very high categories, with no students categorized as having low motivation. Specifically, 60.7% of students were in the very high category, 28.6% in the high category, and 10.7% in the moderate category. Grade IV had the highest percentage in the very high category (77.8%), followed by grade III (54.5%), while grade V showed a balanced distribution between high and very high categories. These findings indicate that students exhibit strong interest and drive in learning Natural Science, which may be influenced by instructional methods, classroom environment, and teacher support. The results provide a positive outlook on the learning climate of Natural Science at the elementary school level and can serve as a basis for designing more engaging and motivational instructional strategies.